3D simulations of pool boiling above smooth horizontal heated surfaces by a phase-change lattice Boltzmann method. (March 2019) - Ma, Xiaojing; Cheng, Ping
Highlights: Dry spot dynamics and liquid-vapor distribution during boiling are simulated. Effects of heater thickness and wettability on boiling heat transfer are investigated. Heat transfer mechanisms at low and high wall superheats are studied. Abstract: Pool boiling heat transfer from smooth horizontal hydrophilic and hydrophobic heaters having a finite thickness under constant bottom wall temperature conditions is simulated numerically with a three-dimensional liquid-vapor phase-change lattice Boltzmann method. For a small heater, single bubble dynamics and temporal variations of heater's top wall temperature in contact with the bubble are investigated. It is found that top wall temperature drops during initial bubble growth period at low wall superheats on a hydrophilic heater due to the microlayer evaporation process. Because of a residual bubble is left on the top of the heater after bubble departure, no wall temperature drop is found on a hydrophilic surface at high wall superheats nor on a hydrophobic surface at any wall superheats. 3D pool boiling curves in dimensionless forms for smooth horizontal heaters of infinite extent from nucleation to critical heat flux through transition boiling to stable film boiling are presented. It is found that 2D and 3D simulated heat fluxes are identical in nucleate boiling and stable film boiling regimes, although transition boiling heat fluxes differ greatly. It is also found that the 3D simulated CHF is in better agreement with existing theories and correlation equations than 2D simulated CHF. Detailed 3D multiple bubbles dynamics above hydrophobic and hydrophilic surfaces and temporal variations of dry spots distribution on these surfaces at CHF are presented. Effects of wettability and thickness of the heater on boiling curves for smooth heaters are investigated. It is founded that only wettability play predominate roles in nucleate boiling regime from smooth superheated surfaces while all factors influence the transition boiling regime (including maximum and minimum heat fluxes) greatly.